Kewenangan dan Pengawasan Pemerintah dalam Regulasi Pembentukan Koperasi Desa Merah Putih - Simorangkir, Debora Juliani; Sinaga, Parbuntian; Setyowati, Retno Kus (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
In the Indonesian economic system, cooperatives play a crucial role as one of the pillars of the national economy, as mandated in Article 33 paragraph (1) of the 1945 Constitution of the Republic of Indonesia. This article emphasizes that "the economy is structured as a joint venture based on the principle of kinship," which serves as the constitutional basis for the existence and development of cooperatives in Indonesia. The research method used in this study is normative juridical, focusing on legal frameworks and regulations related to cooperatives. The results of the study indicate that the government holds an important and strategic role in regulating and supervising cooperatives to ensure the protection of the rights and obligations of cooperative members. Through regulatory instruments such as Law Number 25 of 1992 concerning Cooperatives, the government establishes cooperative principles, good governance standards, and oversight and development mechanisms. The government’s efforts are aimed at ensuring the operation of cooperatives is transparent, accountable, and beneficial to all members. Furthermore, the study found that despite these regulatory efforts, significant challenges remain in the cooperative sector. These include issues such as weak financial reporting, low literacy rates among cooperative members, and the dominance of local elites, which can hinder the equitable distribution of benefits. These challenges need to be addressed to ensure that cooperatives can fulfill their role as economic agents that contribute to national development in line with the principles of kinship and mutual benefit.